Perlindungan Hukum Debitur Dalam Penyelenggaraan Finansial Peer To Peer Lending : Perlindungan hukum terhadap debitur dalam penyelenggaraan finansial berbasis teknolongi dalam peer to peer lending - Amos Sipahutar; Muskibah Muskibah (Zaaken: Journal of Civil and Business Law, 2021)
This study aims to identify and analyze legal protection against debtors in the implementation of technology-based finance in Peer to Peer Lending and the form of settlement of cases between debtors and providers of technology based on peer to peer lending There are also formulations of problems that will be discussed in this study: (1) What is the legal protection for debtors in Financial Technology-based lending and borrowing agreements through Peer to Peer Lending? (2) What is the form of settlement of cases between debtors and providers of peer to peer-based technology? peer lending. In responding to this case, this research uses a doctrinal study with a statutory and conceptual approach. This legal protection is tried on a preventive basis, this legal protection is tried before the formation of the case. Legal protection for users of Peer to Peer Lending-based Fintech services has not yet formed a case, it can be tried with the efforts of Fintech service providers. The organizers' efforts before the formation of the case was to practice the basic principles of legal protection for users of Fintech services. These principles are regulated in article 29 of POJK No. 77/POJK. 01/2016 Regarding data technology-based lending and borrowing services, including the principles of transparency, fair treatment, reliability, confidentiality and information security, as well as simple, fast and affordable settlement of user cases. Abstrak Penelitian ini bertujuan buat mengetahui serta menganailisis proteksi hukum terhadap Debitur dalam penyelenggaraan finansial berbasis teknologi dalam Peer to Peer Lending dan wujud penyelesaian perkara antara Debitur dan penyelenggara teknologi berbasis Peer to peer lending. Ada pula rumusan permasalahan yang hendak dibahas dalam studi ini adalah:(1) Bagaimanakah perlindungan hukum terhadap debitur dalam perjanjian pinjam meminjam uang berbasis Financial Technology melalui Peer to Peer Lending?.(2) Bagaimanakah wujud penyelesaian perkara antara Debitur serta penyelenggara teknologi berbasis Peer to peer lending. Dalam menanggapi kasus tersebut, penelian ini mengenakan jenis studi doktrinal dengan pendekatan peraturan perundang- undangan serta pendekatan konsep. Perlindungan hukum yang dicoba secara preventif, proteksi hukum ini dicoba saat sebelum terbentuknya perkara. Proteksi hukum untuk pengguna layanan Fintech berbasis Peer to Peer Lending belum terbentuknya perkara bisa dicoba dengan upaya- upaya dari penyelenggara layanan Fintech. Upaya penyelenggara saat sebelum terbentuknya perkara yaitu dengan mempraktikkan prinsip dasar perlindungan hukum untuk pengguna layanan Fintech. Prinsip- prinsip tersebut diatur pada pasal 29 POJK No 77/ POJK. 01/ 2016 Tentang layanan pinjam meminjam duit berbasis teknologi data anatara lainprinsip transparansi, perlakuan yang adil, keandalan, kerahasiaan dan keamanan informasi, serta penyelesaian perkara pengguna secara sedernaha, kilat serta bayaran terjangkau.